RGDS- and SIKVAVS-Modified Superporous Poly(2-hydroxyethyl methacrylate) Scaffolds for Tissue Engineering Applications - Macková, Hana; Plichta, Zdeněk; Proks, Vladimír; Kotelnikov, Ilya; Kučka, Jan; Hlídková, Helena; Horák, Daniel; Kubinová, Šárka; Jiráková, Klára (Macromolecular bioscience, 2016)
Three-dimensional hydrogel supports for mesenchymal and neural stem cells (NSCs) are promising materials for tissue engineering applications such as spinal cord repair. This study involves the preparation and characterization of superporous scaffolds based on a copolymer of 2-hydroxyethyl and 2-aminoethyl methacrylate (HEMA and AEMA) crosslinked with ethylene dimethacrylate. Ammonium oxalate is chosen as a suitable porogen because it consists of needle-like crystals, allowing their parallel arrangement in the polymerization mold. The amino group of AEMA is used to immobilize RGDS and SIKVAVS peptide sequences with an N-γ-maleimidobutyryloxy succinimide ester linker. The amount of the peptide on the scaffold is determined using 125 I radiolabeled SIKVAVS. Both RGDS- and SIKVAVS-modified poly(2-hydroxyethyl methacrylate) scaffolds serve as supports for culturing human mesenchymal stem cells (MSCs) and human fetal NSCs. The RGDS sequence is found to be better for MSC and NSC proliferation and growth than SIKVAVS.
Keywords: Tissue Engineering; Humans; peptide; tkáňové inženýrství; RGD; Oligopeptides; Neural Stem Cells; Tissue Scaffolds; IKVAV; lidé; oligopeptidy; buněčné linie; nervové kmenové buňky; Methylmethacrylates; tkáňové podpůrné struktury; Cell Line; mezenchymální kmenové buňky; poly(2-hydroxyethyl methacrylate); stem cell; methylmetakryláty; Mesenchymal Stem Cells